Investigating and preventing sport-related ankle sprain injury - Fong, D. T. P. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Ankle sprain injury is very common in sports. It is worth investigating and preventing it. From the literature, two aetiologies were identified: (1) incorrect landing posture, and (2) delayed peroneal muscle reaction. To investigate the injury mechanism, a model-based image-matching motion analysis technique was developed to analyze real injury incidents captured in televised events. The study provided data for establishing a threshold to identify ankle sprain injury hazard by the inversion velocity as monitored by a uni-axial gyrometer. To prevent the injury, a myoelectric stimulation system was developed to initiate peroneal muscle contraction in a very short time (within 25ms) to accommodate the injurious motion (within 50ms) before the muscle could react (60-90ms). The invention will be commercialized as a prophylactic sport apparel in the coming years